Perbandingan Metode Fuzzy dan Metode Perceptron untuk Mengecek Status Gizi pada Anak - Octaviera Veronica (Ultimatics : Jurnal Teknik Informatika, 2014)
Nutrition status for children was very core factor that need attention from their parent since they are toddlers. In this phase, parents had to know every nutrition that their babies need and nutrition status. For overcome this problem, this application was made. This application was made with fuzzy or perceptron method. This application need some input like weight, height, and age. This means nutrition status was affected by weight, height, and age of that child. If the calculation did by fuzzy method, this calculation will be easier to do, because fuzzy method was more simple so easier to understand. Perceptron method was more complex because this method needs learning some samples with actual data, so need training and testing phase before this application could be used properly. Index Terms-nutrition status, fuzzy, perceptron, JST, food intake, malnutrition